Exploration of the antitumor activity and related mechanisms of RAD5 on colon cancer HT29 Cells - Wei Liqun; Xu Chengfei; Pan Xiaohang; Ruan Guotian; Yan Ling; Tang Shuangyi; Gan Jialiang (结直肠肛门外科)
[Objectives] To investigate the antitumor activity and potential mechanisms of rosmarinic acid derivative 5 (RAD5) on colon cancer HT29 cells. [Methods] Colon cancer HT29 cells were treated with different concentrations of RAD5 (0 μmol/L, 12.5 μmol/L, 25 μmol/L, 50 μmol/L, 100 μmol/L, 150 μmol/L) for 36 hours, and cell viability was detected using the MTT assay. Colon cancer HT29 cells were divided into 3 groups and treated with RAD5 for 36 hours with 0 μmol/L, 25 μmol/L and 50 μmol/L respectively, the cell proliferation ability was assessed using a colony formation assay, apoptosis rate was detected by Hoechst 33258 staining and flow cytometry, and the expression of apoptosis-related proteins Bax, Bcl-2, and EGFR/MAPK pathway-related proteins was examined by Western blot. [Results] The results of cell experiments showed that RAD5 could significantly inhibit the proliferation of colon cancer HT29 cells in a concentration-dependent manner. Compared with the control group (0 μmol/L), the clone formation rates of the 25 μmol/L and 50 μmol/L groups were significantly reduced (P<0.001), apoptosis rates increased (P<0.01), Bax expression increased, Bcl-2 expression showed a downward trend, and the expression of EGFR and ERK1/2 proteins in the EGFR/MAPK pathway decreased, while the ratios of p-ERK1/2/ERK1/2 and p-P38/P38 were elevated (P<0.001). [Conclusion] RAD5 exhibits antitumor activity against colon cancer HT29 cell, and its mechanism may be related to inhibiting EGFR expression and activating the phosphorylation of ERK1/2 and P38 in the downstream MAPK pathway, providing experimental theoretical support for its development as an anticancer candidate drug.